If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -7y + 5x + -19y = 0 Reorder the terms: 8x + 5x + -7y + -19y = 0 Combine like terms: 8x + 5x = 13x 13x + -7y + -19y = 0 Combine like terms: -7y + -19y = -26y 13x + -26y = 0 Solving 13x + -26y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '26y' to each side of the equation. 13x + -26y + 26y = 0 + 26y Combine like terms: -26y + 26y = 0 13x + 0 = 0 + 26y 13x = 0 + 26y Remove the zero: 13x = 26y Divide each side by '13'. x = 2y Simplifying x = 2y
| 1/25=x | | -8m-6=-6(1-8m) | | 9[x-9]-3=-4[2x+4] | | 1y-4=0.75y | | 17=x+2x+5 | | Y=0.1x+5 | | -9h-15=95 | | 3(2d-1)=5 | | 5(x-800)=4000 | | (2x-4)2-20=16 | | 15-.75x=13-.50 | | 800(x+5)=4000 | | -32+b=-2(4+b) | | a=-16+120t | | 5(x+800)=4000 | | -3(x+2)=0 | | 6.7+5.2x=-36.9 | | 15x+13+3x(2+(-13))=253 | | 1.4=(x-62.5)/2.5 | | 7u=2v-20 | | (2x)/(5)-(3)/(4)=(5x)/(2) | | -40+6a=4(8a+3) | | 2x+(x-5)=100 | | s-1.3=4.9 | | 1x-4=4x-10 | | 10y+5-5y+20= | | 4(4+x)=10 | | 3x+4=5x+-2.5 | | -2(1x+3)+3=6(1x+4)+6 | | 1.6x+.6=.25-.3 | | X+(5+X)=5.50 | | 18-10=85 |